Implementation of Information and Communication Technology Systems in the State Administrative Law System - Very Y. Londa; Fanley N. Pangemanan; Femmy M. G. Tulusan (International Journal of Artificial Intelligence Research, 2022)
In most cases, the ability of a government to carry out its mission and run its operations hinges on the administrative reality that is the result of administration and its formulation. Achieving the principle of human protection is the overarching goal of the law. Law and administrative law often reach their final conclusions through the imposition of sanctions. In order to protect and strengthen national unity and integrity in accordance with all applicable laws and regulations and in the best interest of the country, the use and application of Information Technology (ITE) must continue to develop. This law was passed in 2008 as part of Law No. 11. Moreover, the government must back the objective by fostering the growth of IT and legal infrastructure and regulations to ensure that IT is used safely to prevent its misuse, respecting the religious and socio-cultural norms of the Indonesian people. When it comes to state administrative law systems, what exactly do "legal actions" mean, and how do electronic and information systems factor into the administration of these systems? Information technology systems, electronic documents, and electronic certificates are used in accordance with legal, social, and philosophical principles as part of Electronic and Information Systems' role in implementing the State Administrative Law System